Orgranochlorines in harbor seal (Phoca vitulina) tissues from the northern Gulf of Alaska - Wang, D. L.; Atkinson, S.; Hoover-Miller, A.; Lee, S. E.; Li, Q. X.; 王德利 (2007)
Polychlorinated biphenyls (PCBs), dichlorodiphenyltrichloroethane (DDT) and its metabolites, heptachlor and hexachlorocyclohexanes (HCHs) were analyzed in the harbor seal (Phoca vitulina) tissues collected from the Gulf of Alaska during 2000-2001. Sigma HCHs (16-728 ng/g lw) and Sigma DDTs (14-368 ng/g lw) were the predominant pollutants followed by Sigma HCHs (0.56-93 ng/g lw) and heptachlor (<= 0.068-6.0 ng/g lw). Concentrations of the above organochlorines (OCs) in the liver, kidney and blubber tissues correlated with ages, sex, body weight and blubber thickness of the harbor seals. The OC concentrations were similar between the samples collected from two different regions - Prince William Sound, and Kodiak Island and Southern Alaska Peninsula. Mean levels of OCs in nursing female adults were much lower than those in male adults, which indicate that lactation transfer OCs from mother seals to newborns. (c) 2006 Elsevier Ltd. All rights reserved.